Endoscopic lung volume reduction in relation to body mass index in patients with severe heterogeneous emphysema - Fernandez-Bussy, Sebastian; Kornafeld, Anna; Labarca, Gonzalo; Abia-Trujillo, David; Patel, Neal M.; Herth, Felix (Respiration, 2020)
Background: In chronic obstructive pulmonary disease (COPD), body mass index (BMI) is significantly lower in the emphysema-dominant type. Endoscopic lung volume reduction (ELVR) is an innovative way of treating severe emphysema. However, the specific associations of low BMI values and outcomes of ELVR is not well-studied. Objectives: We evaluated associations between initial BMI and changes in major outcomes after endobronchial valve (EBV) placement in patients with heterogeneous severe emphysema. Methods: In a retrospective cohort study, patients were divided into 2 groups based on their baseline BMI (higher BMI ≥21 kg/m2 [n = 18] and lower BMI <21 kg/m2 [n = 63]). Demographics, procedure data, pulmonary function test and 6-min-walk test (6MWT), dyspnea score (according to the modified Medical Research Council [mMRC] scale), BODE (BMI, airflow obstruction, dyspnea, exercise capacity) index, and complications were recorded. After 6 months, changes in variables (dWeight and dBMI) were recorded. Results: Comparing the 2 groups, we found the following: a dWeight of –2.34 kg and +3.39 kg (p value <0.01) and a dBMI of –0.74 and +1.99 kg/m2, in the higher BMI and lower BMI group, respectively (p value <0.01). Changes in forced expiratory volume <1 s (FEV1), 6MWT, mMRC score, and BODE index were not statistically significant. The most common complication was pneumothorax. The lower BMI group experienced more complications than the higher BMI group (40 vs. 24%). Conclusion: Baseline BMI is relevant when selecting candidates for ELVR. Our results show that the COPD patients with a lower BMI gained a significant amount of weight, thus increasing their BMI after the procedure. The rate of complications was higher in the lower BMI group. These findings should alert physicians and encourage nutritional assessment in this population.
Gesehen am 12.10.2020